Optimal sizing and sensitivity analysis of a battery-supercapacitor energy storage system for electric vehicles. (15th April 2021) - Zhu, Tao; Wills, Richard G.A.; Lot, Roberto; Kong, Xiaodan; Yan, Xingda
Abstract: This paper presents a sizing method with sensitivity analysis for battery-supercapacitor hybrid energy storage systems (HESSs) to minimize vehicle-lifetime costs. An optimization framework is proposed to solve joint energy management-sizing optimization. Sensitivity analysis is performed using eight parameters of the vehicle, HESS system and components as sensitive factors. We explain why HESS sizing is sensitive to each factor by discussing the change of optimal HESS size and costs with varying factor values. The relative importance of each factor in practical engineering is quantified and compared. Results show that battery degradation accounts for around 89% of HESS costs; among eight sensitive factors, vehicle driving range has the biggest impact on HESS costs with a calculated impact degree of 1.243. By analyzing comprehensive factors in optimization of HESS sizing, it is expected to provide general a sizing guide applicable to various application scenarios of HESS in electric vehicles. Highlights: Financial costs of using a HESS over vehicle lifetime are formulated with HESS size. An optimization framework is proposed to solve joint sizing-EM optimization. Eight factors of the EV, HESS and components are used in sensitive analysis. Trends of optimal HESS size and financial costs with sensitive factors are revealed. Relative importance of each factor is discussed in terms of practical engineering.